2017
DOI: 10.1007/s12672-017-0293-6
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticulate Tetrac Inhibits Growth and Vascularity of Glioblastoma Xenografts

Abstract: Thyroid hormone as L-thyroxine (T4) stimulates proliferation of glioma cells in vitro and medical induction of hypothyroidism slows clinical growth of glioblastoma multiforme (GBM). The proliferative action of T4 on glioma cells is initiated nongenomically at a cell surface receptor for thyroid hormone on the extracellular domain of integrin αvβ3. Tetraiodothyroacetic acid (tetrac) is a thyroid hormone derivative that blocks T4 action at αvβ3 and has anticancer and anti-angiogenic activity. Tetrac has been cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…Despite the promising chemotherapeutic effects of SN38, its clinical application is relatively hindered by its very low solubility in pharmaceutically accepted media and little stability in physiological pH [16,19]. To overcome such limitations, studies are moved towards attachment of SN38 to hydrophilic polymeric moieties such as EZN-2208 which is PEGylated SN38 in phase 2 clinical trials [20] or its loading into nanoparticles such as liposomes [21], polymeric micelles (NK012 in phase 1 clinical studies) [22] or carbon nanotubes [23]. Such strategies could preserve the stability of the drug moiety while prolonging its blood circulation to enhance the tumour accumulation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the promising chemotherapeutic effects of SN38, its clinical application is relatively hindered by its very low solubility in pharmaceutically accepted media and little stability in physiological pH [16,19]. To overcome such limitations, studies are moved towards attachment of SN38 to hydrophilic polymeric moieties such as EZN-2208 which is PEGylated SN38 in phase 2 clinical trials [20] or its loading into nanoparticles such as liposomes [21], polymeric micelles (NK012 in phase 1 clinical studies) [22] or carbon nanotubes [23]. Such strategies could preserve the stability of the drug moiety while prolonging its blood circulation to enhance the tumour accumulation [15].…”
Section: Introductionmentioning
confidence: 99%
“…The most significant improvement in tumor response was observed with NDAT + cisplatin and XT199 + cisplatin compared to cisplatin alone in orthotopic pancreatic tumor mouse models. NDAT and XT199 alone also had an antitumor effect on pancreatic tumor signal intensity and tumor weight when compared to control (Sudha et al, 2017c;Chang et al, 2018;Li et al, 2019). Doses of NDAT and XT199 were based on previous studies with NDAT or XT199 at 1, 3, and 10 mg/kg s.c., where 10 mg/kg resulted in maximal response.…”
Section: Discussionmentioning
confidence: 99%
“…The latter results imply that T4 action at the integrin may undesirably either decease or not affect expression of these genes. In a limited in vitro study, T3 restricted glioblastoma cell proliferation [42] and preclinical studies have also shown that NDAT-which limits access of T4 to its receptor on integrin αvβ3 on tumor cells-suppresses growth and is anti-angiogenic in glioblastoma xenografts [25].…”
Section: Glioblastomamentioning
confidence: 99%
“…Studies in vitro have disclosed that T4 stimulates the proliferation of breast cancer cells [15][16][17], lung cancer [18,19] and kidney cancer [20] cells, glioblastoma cells [8,21] and other tumor cells [22]. Pharmacologic blockade of T4 action at the integrin is feasible with tetraiodothyroacetic acid (tetrac) and modified forms of tetrac [7,17,20,[23][24][25][26] arrest tumor xenografts.…”
Section: Introductionmentioning
confidence: 99%